PENGARUH SUBTITUSI LIMBAH BATU BATA PADA MORTAR GEOPOLIMER BERBASIS FLY ASH - Harahap, Edwin; Firdaus, Firdaus; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Geopolymer mortar is an alternative way to reduce brick waste (BB) and fly ash (FA) which can pollute the environment. This geopolymer mortar is made from BB and FA because both of these have pozzolanic properties. In this research the bricks were ground and divided based on their respective variations consisting of 0%, 5%, 10%, 15% and with additional ingredients namely sodium hydroxide, sodium silicate, sand and water as activators. There is a difference between the results of the compressive strength of test objects based on days 7, 14, and 28. Some of the compressive strength using a mixture (bricks) were greater and some were smaller. The addition of brick ash can affect the compressive strength of the mortar by a certain percentage. The highest compressive strength at the age of mortar occurs when 15% brick ash is added. On the 7th day it is higher, namely 15% with an average value of 13 Mpa. At 14 days it is 13.5 Mpa. And on the 28th day with an average value of 15.6 Mpa. Meanwhile, the lowest compressive strength occurred with the addition of 5% brick ash. The lowest compressive strength value with a compressive strength of 10.6 Mpa occurred on the 7th day. On the 14th day, it was 11.4 Mpa, and 15.6 Mpa. at the age of 28 days.Keywords: Bricks,Activator,Fly Ash, Geopolymer